Hematology - Latest Research and Clinical Advances 2018
DOI: 10.5772/intechopen.72652
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Biopsy in Multiple Myeloma

Abstract: Liquid biopsies represent an innovative methodology for cancer diagnostics and disease monitoring. The analysis of circulating cell-free nucleic acids (CFNA) and circulating tumour cells (CTC) are rapidly being adopted for quantitative and qualitative characterisation of the tumour genome and as a mode of non-invasive therapeutic monitoring. Circulating cell-free DNA (cfDNA) and CTC are representative of the underlying mutational profile of a cancer whereas the evaluation of extracellular RNA (exRNA) can be ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 119 publications
0
6
0
Order By: Relevance
“…Circulating extracellular vesicles (EVs) containing tumour-specific molecular signatures (oncoproteins, mRNAs, long noncoding RNAs and DNA fragments) have potential clinical utility as next-generation biomarkers for liquid biopsy in cancer diagnosis and management [12][13][14][15][16][17]. In the context of MM, liquid biopsies enable the characterisation of spatial heterogeneity and clonal evolution [18][19][20][21][22][23][24], and may represent an attractive alternative to the single-site tissue biopsies usually employed in the evaluation of MM [19,25,20,21,24,8]. Specifically in MM, a role for large EVs (plEV; EVs shed from the plasma membrane) as predictive or prognostic biomarkers has been demonstrated from patient blood [13,26,27,24], while several key studies have reported the diagnostic potential of small EVs (psEV; EVs with endosomal origin) for MM [26,[28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Circulating extracellular vesicles (EVs) containing tumour-specific molecular signatures (oncoproteins, mRNAs, long noncoding RNAs and DNA fragments) have potential clinical utility as next-generation biomarkers for liquid biopsy in cancer diagnosis and management [12][13][14][15][16][17]. In the context of MM, liquid biopsies enable the characterisation of spatial heterogeneity and clonal evolution [18][19][20][21][22][23][24], and may represent an attractive alternative to the single-site tissue biopsies usually employed in the evaluation of MM [19,25,20,21,24,8]. Specifically in MM, a role for large EVs (plEV; EVs shed from the plasma membrane) as predictive or prognostic biomarkers has been demonstrated from patient blood [13,26,27,24], while several key studies have reported the diagnostic potential of small EVs (psEV; EVs with endosomal origin) for MM [26,[28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Liquid biopsies represent less invasive diagnostic alternatives or additions to single site tissue biopsies, being able to capture the spatial and temporal tumor heterogeneity -a major limitation of tissue biopsies [16][17][18][19][20]. The latter are often invasive or not feasible due to patient compliance/capacity (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…location, size, type/subtype) characteristics [21][22][23][24][25][26]. Conversely, liquid biopsies are innovative tools in precision medicine and cancer diagnostics with the ability to detect, monitor and characterize tumors in a minimally invasive and repeatable way [16][17][18][19][20][27][28][29][30][31]. It is well established that tumor cellderived proteins, nucleic acids and extracellular vesicles (EVs), enter the circulation and reach distant sites where they establish a favorable microenvironment for tumor expansion [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…This variation in outcome is Abbreviations: MM, multiple myeloma; EVs, extracellular vesicles; EV-RNA, extracellular vesicles-derived RNA; PCs, plasma cells; BM, bone marrow; ctDNA, circulating tumour DNA; exRNA, cell-free or extracellular RNA; TME, tumour microenvironment; RBPs, RNA binding proteins; mRNA, messenger RNAs; lncRNA, long non-coding RNAs; miRNA, micro-RNAs; ERCC, Extracellular RNA Communication Consortium; BMME, bone marrow microenvironment; MGUS, monoclonal gammopathy of undetermined significance; SMM, smouldering multiple myeloma; HMCL, human myeloma cell lines; MSC, mesenchymal stromal cells; CAF, cancer associated fibroblasts; FAP, fibroblast-activated protein; a-SMA, asmooth muscle actin; SDF-1, stromal-derived factor 1; HD, healthy donor; ECs, endothelial cells; FIH-1, factor-inhibiting hypoxia-inducible factor 1; PI, proteasome inhibitor. mirrored by the highly (genetically) heterogeneous nature of the disease, both spatially and temporally (6) with multiple foci of disease at diagnosis containing sub-clones that evolve genetically over time contributing to drug resistance (3). Recently, analyses of body fluids including blood (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…liquid biopsies) have generated significant interest due to their potential for the characterisation of tumours with a rapid and non-invasive procedure (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). In the context of MM, accumulating evidence suggest that liquid biopsy captures the genetic heterogeneity of the disease with important implications for circulating tumour DNA (ctDNA) and cell-free or extracellular RNA (exRNA) as valuable markers for tumour genome characterisation, prognostication and sequential monitoring of disease (6)(7)(8)(9)(10)(11)(12)(13). For these reasons liquid biopsies hold promise as an alternative or addition to single-site BM biopsies that are invasive and fail to capture MM tumour heterogeneity (19).…”
Section: Introductionmentioning
confidence: 99%